60 hybrids selected to be evaluated in the 2019 collaborative evaluation network of MasAgro. - CGIAR Research Program on Maize (2019)
60 CIMMYT hybrids were selected and evaluated in 31 to 36 localities of Mexico in 2019. Thirteen hybrids excelled in the results of this evaluation for their high yield potential and agronomic characteristics. It will be decided which hybrids could be released at the end of 2020.